Development and testing of a web module to IMPROVE generic prescribing of oral contraceptives among primary care physicians. (1st June 2019) - Lenti, Gena; Norenberg, Allison; Farnan, Jeanne M.; Weissman, Arlene; Cook, Michelle; Shah, Neel; Moriates, Christopher; Wallingford, September; Lynch, Shalini; Stebbins, Marilyn; Millard, Steven; Samarth, Anita; et al.
Abstract: What is known and objective: The use of generic oral contraceptives (OCPs) can improve adherence and reduce healthcare costs, yet scepticism of generic drugs remains a barrier to generic OCP discussion and prescription. An educational web module was developed to reduce generic scepticism related to OCPs, improve knowledge of generic drugs and increase physician willingness to discuss and prescribe generic OCPs. Methods: A needs assessment was completed using in‐person focus groups at American College of Physicians (ACP) Annual Meeting and a survey targeting baseline generic scepticism. Insights gained were used to build an educational web module detailing barriers and benefits of generic OCP prescription. The module was disseminated via email to an ACP research panel who completed our baseline survey. Post‐module evaluation measured learner reaction, knowledge and intention to change behaviour along with generic scepticism. Results and discussion: The module had a response rate of 56% (n = 208/369). Individuals defined as generic sceptics at baseline were significantly less likely to complete our module compared to non‐sceptics (responders 9.6% vs non‐responders 16.8%, P  = 0.04). The majority (85%, n = 17/20) of baseline sceptics were converted to non‐sceptics ( P  < 0.01) following completion of the module. Compared to non‐sceptics, post‐module generic sceptics reported less willingness to discuss (sceptic 33.3% vs non‐sceptic 71.5%, P  < 0.01), but not less willingness to prescribe generic OCPs (sceptic 53.3% vs non‐sceptic 67.9%, P  = 0.25). Non‐white physicians and international medical graduates (IMG) were more likely to be generic sceptics at baseline (non‐white 86.9% vs white 69.9%, P  = 0.01, IMG 13.0% vs USMG 5.0% vs unknown 18.2%, P  = 0.03) but were also more likely to report intention to prescribe generic OCPs as a result of the module (non‐white 78.7% vs white 57.3%, P  < 0.01, IMG 76.1% vs USMG 50.3% vs unknown 77.3%, P  = 0.03). What is new and conclusion: A brief educational web module can be used to promote prescribing of generic OCPs and reduce generic scepticism. Abstract : The goal of this study is to develop an educational web module aimed at reducing scepticism of generic oral contraceptive pills (OCPs), increasing knowledge of generic OCPs, and increasing willingness to discuss and prescribe generic OCPs. The module identified groups with low knowledge and high scepticism of generic OCPs to target for further interventions.